Measuring the rates of feed degradation in the rumen - Pezo, Danilo A. (Inter-American Institute for Cooperation on Agriculture, 1992)
Outlines the measuring rates of feed degradation in the rumen, w. ref. to parameters used in ruminal degradation kinetics; models used for the estimation of ruminal degradation rates; and the application of the information provided by feed degradation rate studies.